Development and validation of the facilitative interpersonal skills scale for clients - Santos, João M. (2022)
psychotherapist development, psychotherapy expertise, statistical methodology, test development, therapist effects1| INTRODUCTION The role of the therapist in psychotherapy research has a controversial history. The widespread focus on investigating specific treatment protocols for specific psychological disorders made the study of individual differences among therapistsalong‐neglected research topic (e.g., Beutler et al.,2004;Castonguay&Hill,2017). However, despite the historicallygreater emphasis on randomized controlled trials to understand differences between specific treatment models, researchhas consistently shown thattherapistscontribute more to therapy outcomes than the type of treatment or level ofadherence to a particular protocol (Wampold & Imel,2015). It seems that therapist effects can explain 5%–9% of theoutcome variance (Baldwin & Imel,2013). These results overshadow the 0%–1% variability attributable to specifictreatment models (Miller et al.,2013; Wampold & Imel,2015).The existing literature suggests that the therapeutic alliance is one of the best predictors of clinical outcomes identified to date, along with the therapist's ability to convey empathy (Nor cross &Lambert,2019; Nor cross & Wampold,2019; Wampold & Imel,2015). The therapeutic alliance is described by Bordin (1979) as a collaborative relationship intended to overcome the client's suffering. This relation shipe incompasses three important aspects: (a) agreement on the goals of the treatment, (b) agreement on thetasks, and (c) the development of a mutual bond betweentherapist and client. The therapeutic alliance isconsidered a common factor or a nonspecific factor in psychotherapy. These factors include therapeuticqualities (such as empathy and the therapist's ability to be persuasive and to create compelling expectations)foundintherapistsandprofessionalsacrosstherapeutic approaches and helping professions (Frank &Frank,1993).Commonfactorsaresubjecttovariousdefinitionswhichposessomechallengestocontrolledexperimental research (Anderson & Patterson,2013). Following the need to measure and operationalizethese factors, Anderson and Patterson (2013) created the facilitative interpersonal skills (FIS) rating scale,which assesses several relational therapist skills relevant to therapeutic effectiveness (Anderson &Patterson,2013). These skills play an important role in the ability to develop and maintain a solid therapeutic alliance and might go beyond the therapist's use of a particular treatment model or technique(Wampold & Imel,2015).The FIS rating scale (Anderson & Patterson,2013)isaperformance‐based measure of eight therapist interpersonalskills, namely verbal fluency, emotional expression, persuasiveness, warmth/positive regard, hopefulness, empathy, alliancebond capacity, and alliance–rupture–repair responsiveness. This measure was designed for the assessment of thetherapist's performance by an external observer. More specifically, it evaluates participants' responses to a performance‐based task where they provide therapeutic responses to standardvideostimulithatportraychallenging psychotherapeuticevents. In these clips, one actor/actress plays the role of a client explaining a certain problem to which the participantshave to respond in a therapeutic manner as if they were in session. The FIS‐in session (FIS‐IS) rating scale (Uhlin,2011)isan adaptation of the original FIS ratingscale applied to actual recorded or observed therapy sessions. Similarly to theoriginal FIS, an external coder rates the therapist's performance. Our goal is to create a new FIS scale (the FIS‐clientversion [FIS‐C]) where clients evaluate their therapists' performance.Anderson et al. (2009) found that therapists' observer‐rated FIS predicted those therapists' real‐lifeclinical outcomes. Subsequent studies confirmed that FIS scores predicted outcome and alliance (Anderson,Crowley, et al.,2016; Anderson, McClintock, et al.,2016) and that these skills were trainable throughdeliberate practice(Anderson et al.,2020;Rousmaniereetal.,2017). The effects of observer‐rated therapist 2|SANTOS ET AL.